2019
DOI: 10.2503/hortj.okd-si01
|View full text |Cite
|
Sign up to set email alerts
|

Protected Horticulture after the Great East Japan Earthquake in Iwate Prefecture

Abstract: Agricultural lands in the Kesen area, which is located in the coastal area of Iwate Prefecture, were severely damaged by the Great East Japan Earthquake on March 11, 2011. Empirical research was undertaken to promote agricultural restoration and reconstruction. This project was conducted to realize low-cost protected horticulture utilizing local resources effectively. In this area, where forestry was popular, there was abundant unnecessarily thinned timber. Three types of low-cost greenhouses were developed, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…As results, they did not focus to manage their farms, but to rebuild and reconstruct their houses. Significant and critical efforts need to be taken to address the adverse impacts and bring the agricultural production into normal such as those reported by Japanese researchers to address the adverse impacts of big earthquake in Japan in 2011 [14][15][16]. The findings on the impacts COVID-19 pandemic found in this study are also consistent with the findings reported by other researchers on the impacts of COVID-19 on agriculture [17][18][19][20][21][22][23][24][25][26][27].…”
Section: Discussionsupporting
confidence: 86%
“…As results, they did not focus to manage their farms, but to rebuild and reconstruct their houses. Significant and critical efforts need to be taken to address the adverse impacts and bring the agricultural production into normal such as those reported by Japanese researchers to address the adverse impacts of big earthquake in Japan in 2011 [14][15][16]. The findings on the impacts COVID-19 pandemic found in this study are also consistent with the findings reported by other researchers on the impacts of COVID-19 on agriculture [17][18][19][20][21][22][23][24][25][26][27].…”
Section: Discussionsupporting
confidence: 86%
“…As the appearance and taste of the imported fruits are not highly appreciated in the Japanese market, in addition to concerns on pesticide application and post-harvest treatments abroad, domestically produced strawberries are preferred (Imada, 2007). Therefore, everbearing strawberries are planted in cold areas for off-seasons to increase the production of domestic strawberries in summer and autumn (Yamazaki, 2015;Ohta and Yasuba, 2019). On the other hand, as confectioneries claim that everbearing strawberries have a poorer taste than that of June-bearing strawberries (Shibuya, 2010;Hamano et al, 2020), they want a year-round stable supply of June-bearing strawberries.…”
Section: Introductionmentioning
confidence: 99%